Lithuanians among prisoners of other ethnic groups in special-purpose camps of USSR MGB - Allanijazov, Turganbek (Genocidas ir rezistencija, 2018)
Turganbek Allanijazov (the Republic of Kazakhstan, O. A. Baikonurov Zhezkazgan University), the author of this article, explores main statistical data related to the number of Lithuanians in special purpose camps of The Chief Administration of Corrective Labour Camps (GULAG) under the Ministry of State Security (MGB) of the Union of Soviet Socialist Republics (USSR), located in the territories of the Kazakh Soviet Socialist Republic and Russian Soviet Federative Socialist Republic (RSFSR), in 1950–1954. Quantitative dynamics of Lithuanians is presented by years and camps. Tendencies and trends of quantitative change are shown. Camps with the greatest number of Lithuanians are specified, as well as those with the least number. The date within the lifetime period of camps known for the greatest number of Lithuanians as prisoners is indicated.
Keywords: soviet Lithuania; political prisoners; repressions; Gulag; concentration camp